Ab initio potential energy functions, spectroscopy and thermal physics for krypton-contained rare gas dimers. (September 2022) - Hu, Yurong; Zhai, Yu; Li, Hui; McCourt, Frederick R.W.
Highlights: The state-of-the-art ab initio interatomic potential energy functions (PEFs) and dipole moment functions (DMFs) for the Kr-Ne, Kr-Ar, and Kr-Xe rare gas dimers are developed. Ro-vibrational energy levels and absorption spectra are predicted and in good agreement with experimental values. The thermophysical properties of dilute gases are computed from theoretical work and obtain accurate values which are good agree with the experimental data Abstract: Three state-of-the-art ab initio interatomic potential energy functions (PEFs) for the Kr-Ne, Kr-Ar, Kr-Xe rare gas dimers are presented. These PEFs are based upon extrapolation to complete basis set (CBS) limit results of supermolecular computations at the coupled-cluster level with single, double, and perturbative triple excitations (CCSD(T)) and correlation-consistent basis sets up to sextuple-zeta quality, augmented with mid-bond functions. Core-core and core-valence electron correlation, higher-order coupled-cluster excitations up to perturbative quadruple excitations, CCSDT(Q), and scalar relativistic corrections have also been taken into account. We have employed Morse/Long Range (MLR) potential energy functions (PEFs) to fit the total interaction energies as a function of the internuclear separation, followed by the calculation of spectroscopic parameters, vibrational and rotational energy levels, absorption spectra, and thermophysical properties over an extensive temperature range. Good agreement with experimental data and an empirical potential energy function shows that our ab initio MLR PEFs are superior not only to previous PEFs, but also to most empirical PEFs.